2017
DOI: 10.1016/j.cca.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

3′-UTR SNP rs2229611 in G6PC1 affects mRNA stability, expression and Glycogen Storage Disease type-Ia risk

Abstract: The frequency of rs2229611, previously reported in Chinese, Caucasians, Japanese and Hispanics, was investigated for the first time in Indian ethnicity. We analyzed its role in the progression of Glycogen Storage Disease type-Ia (GSD-Ia) and breast cancer. Genotype data on rs2229611 revealed that the risk of GSD-Ia was higher (P=0.0195) with CC compared to TT/TC genotypes, whereas no such correlation was observed with breast cancer cases. We observed a strong linkage disequilibrium (LD) among rs2229611 and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…Meanwhile, our results also proved that the c.2327A>G mutation in the 3′‐UTR influences ARE‐mediated mRNA decay of Hu sheep FSHR gene. This is consistent with the polymorphisms in the 3′‐UTR of other ARE‐containing transcripts such as IFNL3 (McFarland et al, ), G6PC1 (Karthi et al, ) and SLC4A4 (Patel et al, ). A more recent report showed that a novel mutation in the 3′‐UTR of human SLC4A4 gene creates an ARE motif and enhances SLC4A4 interaction with the zinc finger protein ZFP36/TTP, an ARE‐mRNA decay‐promoting protein, thereby leading to destabilization and rapid degradation of the SLC4A4 transcript (Patel et al, ).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Meanwhile, our results also proved that the c.2327A>G mutation in the 3′‐UTR influences ARE‐mediated mRNA decay of Hu sheep FSHR gene. This is consistent with the polymorphisms in the 3′‐UTR of other ARE‐containing transcripts such as IFNL3 (McFarland et al, ), G6PC1 (Karthi et al, ) and SLC4A4 (Patel et al, ). A more recent report showed that a novel mutation in the 3′‐UTR of human SLC4A4 gene creates an ARE motif and enhances SLC4A4 interaction with the zinc finger protein ZFP36/TTP, an ARE‐mRNA decay‐promoting protein, thereby leading to destabilization and rapid degradation of the SLC4A4 transcript (Patel et al, ).…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, both ARE1 and ARE2 motifs in the 3′‐UTR are all involved in mRNA decay of Hu sheep FSHR gene (Figure g). Together, our findings further demonstrated the importance of AREs in the regulation of expression of the ARE‐containing transcripts (Chen & Shyu, ; Karthi et al, ; Patel et al, ). Meanwhile, our results also proved that the c.2327A>G mutation in the 3′‐UTR influences ARE‐mediated mRNA decay of Hu sheep FSHR gene.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations